Systemic and breath biomarkers for asthma: an update. Issue 1 (February 2020) - Mogensen, Ida; James, Anna; Malinovschi, Andrei
Abstract : Purpose of review: Finding suitable biomarkers to phenotype asthma, identify individuals at risk of worsening and guide treatment is highly prioritized in asthma research. We aimed to provide an analysis of currently used and upcoming biomarkers, focusing on developments published in the past 2 years. Recent findings: Type 2 inflammation is the most studied asthma mechanism with the most biomarkers in the pipeline. Blood eosinophils and fractional exhaled nitric oxide (FeNO) are those most used clinically. Recent developments include their ability to identify individuals at higher risk of exacerbations, faster decline in lung function and more likely to benefit from anti-IL-5 and anti-IL-4/-13 treatment. Certain patterns of urinary eicosanoid excretion also relate to type 2 inflammation. Results of recent trials investigating the use of serum periostin or dipeptidyl peptidase-4 to guide anti-IL-13 therapy were somewhat disappointing. Less is known about non-type 2 inflammation but blood neutrophils and YKL-40 may be higher in patients with evidence of non-type 2 asthma. Volatile organic compounds show promise in their ability to distinguish both eosinophilic and neutrophilic asthma. Summary: The ultimate panel of biomarkers for identification of activated inflammatory pathways and treatment strategies in asthma patients still lies in the future, particularly for non-type 2 asthma, but potential candidates are available.